Effect of colistin and tylosin used as feed additives on the performance, diarrhea incidence, and immune response of nursery pigs - Kelly Mazutti; Leandro Batista Costa; Lígia Valéria Nascimento; Tobias Fernandes Filho; Breno Castello Branco Beirão; Pedro Celso Machado Júnior; Alex Maiorka (Semina: Ciências Agrárias, 2016)
For the last several decades, antimicrobial compounds have been used as feed additives to promote piglet growth at weaning, through the prevention of subclinical and clinical disease. However, few studies have assessed the influence of these antibiotics on the immune response of nursery pigs, as well as the relation between performance, health, and immunity of animals that receive feed additives. Therefore, the present study aimed to evaluate the effects of colistin and tylosin when used as feed additives on the performance, incidence of diarrhea, and immune response of nursery pigs. In this study, 72 weaned pigs (average age, 28 days) were allotted into one of three treatment groups: a control group (feed with no antibiotics), tylosin group (feed containing 22 ppm tylosin), and colistin group (feed containing 20 ppm colistin). Weekly, during a five week period, the average daily feed intake, average daily gain, and feed conversion ratio of the pigs were evaluated. Stools were scored daily, in accordance with a fecal texture scale. Blood samples were collected on the day of housing (d0) and on d7, d21, d28, and d35 for immune cell phenotyping. The results of this study showed that piglets in both the colistin and tylosin groups exhibited a significantly higher average daily feed intake, resulting in a higher body weight at the end of the experimental period (d35) when compared with piglets from the control group. Colistin and tylosin also significantly reduced the incidence of diarrhea. Colistin and tylosin modulated the piglets’ immune responses, particularly on d28, by changing the percentage of circulating B lymphocytes, CD4+CD8+ T cells, and the CD4:CD8 ratio.